Innovation Strategy of Village-Owned Enterprises in Improving Local Potential and Economic Welfare of Kalidawir Village Community, Tanggulangin District - Dainy, Zilba Vara; Fitriyah, Hadiah (CV. Media Digital Publikasi Indonesia, 2025)
BUMDes has an important role as a representation of the Village Government, so that it can make a maximum contribution in an effort to overcome various economic problems. In the BUMDes innovation strategy with the Triple Helix approach to increase local potential and welfare of Kalidawir Village, Tanggulangin Subdistrict using descriptive qualitative research methods. Key informants in this study were the Kalidawir village head and other supporting informants, Data collection techniques through observation, interviews, and documentation. Data analysis techniques through the stages of data collection, data analysis, and conclusion drawing. The results of this study indicate that triple helix collaboration in the innovation strategy of Village-Owned Enterprises requires strong collaboration between universities, the private sector, and the government. Lack of coordination, differences in goals and interests, as well as difficulties in balancing the roles of each party, are challenges that must be faced by all elements of the triple helix.